Penyusunan Strategi Pemberdayaan GP3A untuk Peningkatan Partisipasi Pada O&P Jaringan Utama Sistem Irigasi - - Murtiningrum; Suci Ristiana; Yuli Wahyuningtyas (Jurnal Irigasi, 2014)
It is possible for farmers, through Federation of Water Users’ Association (WUAF), as direct users to participate in the management of the irrigation system main network. The government of Yogyakarta Special Region (DIY) encourages WUAF to participate in the main network management so farmers understand the system comprehensively so that irrigation will be better managed and sustainably. This paper aimed to assess WUAF participation in irrigation system management as well as to identify factors influenced the participation level and to formulate strategies to improve WUAF participation. Based on their performances, WUAFs were clustered into three clusters, namely cluster 1 for WUAFs with good performance in all aspects, cluster 2 for WUAFs with financial weakness, and cluster 3 for WUAFs financial and institutional weaknesses. Strategy proposed for cluster 1 was minor government intervention to maintain WUAFs performance. Strategy proposed for cluster 2 and cluster 3 was pursuing independent funding source. Additional strategy for cluster 3 was institution strengthening through routine meetings and field workers. General strategies applicable for all clusters were improvement of WUAF role in the management of main network supported with appropriate training and selection of high-value agricultural commodities.